HUBUNGAN FAKTOR PENGASUHAN DENGAN STUNTING DI KECAMATAN UBUD GIANYAR BALI - Ni Made Dwi Mahayati; Ni Gusti Kompiang Sriasih (COLOSTRUM JURNAL KEBIDANAN, 2020)
Introduction: The quality of a child is also determined by the health status of the child, especially in the toddler period. This period is a golden period for child development, so it is very important to ensure that the child's growth runs optimally, including ensuring that the nutritional status of toddlers is in a good category. The problem of short toddlers illustrates the existence of chronic nutritional problems that can be affected by the condition of the mother during pregnancy, the fetus, infants and toddlers, including diseases suffered during toddlers. This study aimed to analyze the relationship between parenting factors and stunting. Methods: Design of this study was analytic observational with cross sectional approach. The sampling technique used was purposive sampling by taking samples from two areas of stunting loci in Ubud District with a sample size of 92 people. The data collected are primary and secondary data. Data analysis used Chi Square and Fisher's Exact test. Results and Discussion: The results showed that most of the children were in nonstunting status with a stunting rate of 25%. The results of the bivariate analysis between the independent variables and stunting showed the following results: exclusive breastfeeding status (p = 0.01), active posyandu visits (p = 0.022) and diarrhea exposure (p = 1.00). Conclusion: There is a relationship between exclusive breastfeeding status and active posyandu visits with stunting in toddler. Keywords: toddlers, posyandu visits, stunting, exclusive breastfeeding, child infections